A brain sexual dimorphism controlled by adult circulating androgens - Cooke, Bradley M. (The National Academy of Sciences, 1999)
Reports of structural differences between the brains of men and women, heterosexual and homosexual men, and male-to-female transsexuals and other men have been offered as evidence that the behavioral differences between these groups are likely caused by differences in the early development of the brain. However, a possible confounding variable is the concentration of circulating hormones seen in these groups in adulthood. Evaluation of this possibility hinges on the extent to which circulating hormones can alter the size of mammalian brain regions as revealed by Nissl stains. We now report a sexual dimorphism in the volume of a brain nucleus in rats that can be completely accounted for by adult sex differences in circulating androgen. The posterodorsal nucleus of the medial amygdala (MePD) has a greater volume in male rats than in females, but adult castration of males causes the volume to shrink to female values within four weeks, whereas androgen treatment of adult females for that period enlarges the MePD to levels equivalent to normal males. This report demonstrates that adult hormone manipulations can completely reverse a sexual dimorphism in brain regional volume in a mammalian species. The sex difference and androgen responsiveness of MePD volume is reflected in the soma size of neurons there.